Structure and ion physiology of Brasenia schreberi glandular trichomes in vivo - Yang, Chaodong (PeerJ, 2019)
Brasenia schreberi is a critically endangered aquatic basal angiosperm. In this work, we characterized the structure of the glandular trichomes of B. schreberi morphologically and histochemically. We used a variety of structural, histochemical and permeability stains for the characterization, and we tested the effects of stress in vivo using NaCl and ethanol. We observed that the glandular trichome of B. schreberi are composed of two disk-like stalk cells, and a glandular cell which surround a cuticular storage space. The cuticle is discontinuous at the surface of the shoots. Nearly half of young trichomes senesced in 0.9% NaCl, and mature trichomes senesced at 1.8% NaCl. About half of young trichomes senesced under 3% ethanol and mature trichomes senesced in 2% ethanol after 20 min of treatment. The physiology of glandular trichomes affects the way they secrete mucilage via storage space at a young stage. The trichomes become permeable and absorb ions when mature. This transition depends on the osmiophilic material and the dynamic protoplast. It can accelerate senescence and disassembly by ion accumulation. Permeability tests and ion treatments of glandular trichomes provide new insights for fertilizer research. Our study highlights the structure and physiology of B. schreberi glandular trichomes.